Medieval Matters: Europe's Premodern Religious Cultures : Studies in Honour of Miri Rubin - Champion, Matthew (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
Medieval Matters: Europe's Premodern Religious Cultures offers innovative perspectives on Europe's medieval religious landscapes through diverse case studies spanning Livonia to Iberia. This interdisciplinary collection examines the complex interplay of ritual, community, memory, and identity across medieval religious practices, with particular attention to Jewish-Christian relations, gender dynamics, and devotional materiality. Honouring Miri Rubin's transformative scholarship, the volume brings together emerging scholarly voices who engage with her insights on ritual, narrative, emotion, gender, and devotion. The collection concludes with a roundtable of eminent medievalists reflecting on Rubin's influence and future directions for studying the premodern past.